KANTOR URUSAN AGAMA KECAMATAN TORJUN DALAM IMPLEMENTASI UNDANG-UNDANG NOMOR 16 TAHUN 2019 TENTANG PERKAWINAN - Ma’ani, Akh. Roqiqul; Muhaimin, Hikmah; Santosa, Santosa (MAJAPAHIT POLICY, 2024)
This study aims to understand the implementation of Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage, especially in the context of early marriage in Torjun Village, Torjun District, Sampang Regency. Although there have been strict regulations to regulate the age limit for marriage, the phenomenon of early marriage still often occurs in the area. This study uses a descriptive qualitative approach to describe reality accurately through words, using relevant data collection and analysis techniques and obtained from scientific situations to dig deeper into the culture, norms, and social dynamics that influence the sustainability of this practice. This study uses Edward III's Policy Implementation Theory where policy implementation includes four key variables that influence the implementation of public policy, namely communication, resources, disposition and bureaucratic structure. This study is included in the category of descriptive qualitative research because the researcher aims to understand a phenomenon that is part of the culture in Torjun Village, Torjun District, Sampang Regency. Data collection techniques are carried out through observation, interviews, and documentation. The informants interviewed were the Head of the KUA of Torjun District with staff, the Religious Court of Sampang Regency, and the Community. Based on the results of the research that has been carried out, namely in the application or implementation of Law Number 16 of 2019 concerning amendments to Law Number 1 of 1974 concerning marriage which requires men and women to be 19 years old, which in practice the community still carries out many early marriages or under the age of 19 years with several background reasons but the most basic factor is because in the Torjun community the practice of early marriage has been customary and has become a tradition there and in the legal basis itself there is indeed no legal basis for perpetrators of early marriage practices.